The Role of Parents in Watching Generation Alpha Assistance - nurdahlia, dwi ulfa (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
When it is important for parents to maintain the spectacle consumed by children. Judging from the data on mobile users, it is very high. Even from the Ministry of Communication and Information, there are 143.26 million people or 54.68 percent of Indonesia's population using the internet with users aged 13-18 years. Meanwhile, other data from the Minister of Communication and Information Rudiantara revealed that as many as 93.52 percent of internet users, 65.34 percent, are aged 9-19 years. While the latest data from BPS describes data for 2022, as many as 33.44% of early childhood aged 0-6 years in Indonesia are already able to use cell phones, 24.96% of early childhood in the country are also able to access the internet. Parents must be wise in addressing the height of Alpha generation children who were indeed born in the digital era. Of course , people know they have challenges in choosing what to watch. This research uses a descriptive qualitative method which is carried out by observing, interviewing parents who find it difficult to choose shows for their children and parents who experience concerns about children's behavior caused by shows that children see such as YouTube. The results of the study show that not all of the alpha generation are negatively affected by viewing on smartphones and smart TVs. There are other positive impacts, especially if parents play an important role in accompanying children's viewing by conducting parenting mediation.